The Effect of Market Segmentation Strategy On Purchasing Decisions of Panties Pizza In Surabaya - Ananda Dwi Lestari; Agus Baktiono; Ani Wulandari (Quantitative Economics and Management Studies, 2020)
This study aims to analyze the effect of market segmentation strategies on purchasing decisions of Panties Pizza in Surabaya. The type of research is quantitative and SPSS 16 was employed to test the hypotheses with multiple linear regression analysis. The population in this study was the customers of Panties Pizza in Surabaya. The sampling technique used was non probability sampling with a purposive sampling approach with as many as 100 respondents who have purchased Panties Pizza. The results of this study indicated that the variables of geographical segmentation, demographic segmentation, and psychographic segmentation have a significant effect simultaneously on purchasing decisions in Panties Pizza Surabaya. The coefficient of determination is 62% and the rest was influenced by other variables not examined in this study. Geographical segmentation variables had a significant effect partially on the decision to purchase Panties Pizza in Surabaya with a significance value of 0.004 <0.05. Demographic segmentation variables had no significant effect partially on the decision to purchase Panties Pizza in Surabaya with a significance value of 0.722> 0.05. Psychographic segmentation variables had a significant effect partially on purchasing decisions of Panties Pizza in Surabaya with a significance value of 0,000 <0.05. The variables of geographical segmentation, demographic segmentation, and psychographic segmentation that possessed a significant influence psychographic segmentation with value of β = 0.644.